2020
DOI: 10.22271/chemi.2020.v8.i1at.8731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of colored plastic mulching and drip irrigation levels on soil temperature, plant growth and fruit quality of tomato (Solanum Lycopersicum)

Abstract: Plastic mulching has significantly enhanced vegetable production worldwide since the 1950. It is used extensively due to its properties improved soil, plant growth, fruit quality properties and low cost. A field experiment was conducted to evaluate the influence of various color plastic mulches (white on black, silver on black and black on silver) and irrigation levels (60, 80 and 100 per cent ETc) on plant growth parameters and weed suppression in tomato (Solanum lycopersicum) cultivation at Madurai district,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The specific surface area and specific length of the roots were greater in the treatment that used a 1.20 m wide silver mulching, followed by the treatment that used a 1.40 m wide silver mulching, corroborated by results obtained in the research of Sarkar et al (2019). The possible cause is related to the higher amount of available water in the topsoil, caused by low water evaporation, resulting in a concetration of roots in the shallower soil depths, thus forming several fine roots (Jayalalitha et al, 2020).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The specific surface area and specific length of the roots were greater in the treatment that used a 1.20 m wide silver mulching, followed by the treatment that used a 1.40 m wide silver mulching, corroborated by results obtained in the research of Sarkar et al (2019). The possible cause is related to the higher amount of available water in the topsoil, caused by low water evaporation, resulting in a concetration of roots in the shallower soil depths, thus forming several fine roots (Jayalalitha et al, 2020).…”
Section: Resultssupporting
confidence: 74%
“…It rises soil temperature, maintains moisture, and controls weeds. The use of this technology will result in the reduction of soil temperature fluctuation at a 0.20-0.30 m depth, promoting better root development and also reducing fertilizer leaching and soil compaction (Jayalalitha et al, 2020), in addition to increasing the availability of nutrients and providing protection against injuries caused by frost (Pandey et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(2020) [15] also reported that the combination of lower irrigation regime and polythene mulch is more efficient in suppression of weed plants.…”
Section: Resultsmentioning
confidence: 97%
“…(1994) [29] and Jayalalitha et al (2020) [15] with the use of polythene mulch in tomato. The combined effects of irrigation levels and mulch materials significant influenced weed density at all growth stages.…”
Section: Resultsmentioning
confidence: 99%